Characterization of the 3‐D fracture setting of an unstable rock mass: From surface and seismic investigations to numerical modeling. Issue 8 (1st August 2017) - Colombero, C.; Baillet, L.; Comina, C.; Jongmans, D.; Vinciguerra, S.
Abstract: The characterization of the fracturing state of a potentially unstable rock cliff is a crucial requirement for stability assessments and mitigation purposes. Classical measurements of fracture location and orientation can however be limited by inaccessible rock exposures. The steep topography and high‐rise morphology of these cliffs, together with the widespread presence of fractures, can additionally condition the success of geophysical prospecting on these sites. In order to mitigate these limitations, an innovative approach combining noncontact geomechanical measurements, active and passive seismic surveys, and 3‐D numerical modeling is proposed in this work to characterize the 3‐D fracture setting of an unstable rock mass, located in NW Italian Alps (Madonna del Sasso, VB). The 3‐D fracture geometry was achieved through a combination of field observations and noncontact geomechanical measurements on oriented pictures of the cliff, resulting from a previous laser‐scanning and photogrammetric survey. The estimation of fracture persistence within the rock mass was obtained from surface active seismic surveys. Ambient seismic noise and earthquakes recordings were used to assess the fracture control on the site response. Processing of both data sets highlighted the resonance properties of the unstable rock volume decoupling from the stable massif. A finite element 3‐D model of the site, including all the retrieved fracture information, enabled both validation and interpretation of the field measurements. The integration of these different methodologies, applied for the first time to a complex 3‐D prone‐to‐fall mass, provided consistent information on the internal fracturing conditions, supplying key parameters for future monitoring purposes and mitigation strategies. Key Points: The 3‐D fracture setting was achieved combining noncontact measures of cliff and fracture geometry, seismic surveys, and numerical modeling Active seismic surveys provided valuable constraints on fracture location and persistence within the rock mass Passive seismic recordings (seismic noise and earthquakes) highlighted the complex 3‐D fracture‐driven dynamic response of the site